Simulasi Efek Rumah Kaca dalam Skala Laboratorium: Analisis Kenaikan Suhu Menggunakan MATLAB - Gahansa, Tesalonika Yakomina; Kamaruddin, Kamaruddin; Rende, Jeane Cornelda; Silangen, Patricia Mardiana; Londa, Treesje Katrina (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
This study aims to simulate and analyze temperature rise due to the greenhouse effect through a simple experiment and numerical modeling using MATLAB. Two systems—a sealed glass jar (simulating a greenhouse gas-trapping atmosphere) and an open jar (control)—were exposed to sunlight for 30 minutes, with temperature recorded at 5-minute intervals. Experimental results showed that the sealed jar experienced a higher temperature increase (24°C to 28.5°C) compared to the open jar (24°C to 28°C), demonstrating heat trapping. Data were analyzed using MATLAB's Curve Fitting Toolbox for regression modeling and graphical visualization. Numerical simulations exhibited strong consistency with experimental data, confirming the model's accuracy in predicting temperature trends. The study concludes that MATLAB is an effective computational tool for simulating physics phenomena related to global warming while highlighting the urgency of environmental mitigation. These findings can serve as a foundation for developing applied physics experiments or small-scale climate models.